Evaluation of the Performance of Rapid Diagnostic Test and Microscopic Examination for Malaria Detection in Symptomatic Patients in Sorong City, Southwest Papua - Mulya Aisyah; Imam Sucahyo; Haryatmi, Dwi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Malaria parasite examination is conducted by analyzing the blood of individuals suspected of having malaria, either through a rapid method using Rapid Diagnostic Tests (RDT) or through microscopic examination. This study aimed to evaluate the performance of RDT as a fast and practical alternative for malaria diagnosis. An analytical observational design was used, involving 73 patients as respondents. Data collection was carried out through questionnaires and venous blood sampling, followed by RDT testing and microscopic examination. The results showed that RDT had a sensitivity of 81.8% and a specificity of 100%. The study concluded that although RDT is fairly reliable in detecting positive cases (true positives), there are still some undetected cases (false negatives), particularly among individuals with low levels of parasites in their blood (low parasitemia).